Expression, purification, and characterization of a recombinant stem bromelain from ananas comosus - Amid, Azura; Ismail, Nurul Azira; Yusof, Faridah; Mohd. Salleh, Hamzah (ELSEVIER, 2011)
Commercially available bromelain is prepared by performing a tedious and costly purification method that provides multiple degrees of purified bromelain. In the current study, a gene encoding stem bromelain from Ananas comosus was amplified using polymerase chain reaction (PCR). This bromelain gene was initially cloned into pENTR/TEV/D-TOPO before being sub-cloned into the expression vector pDEST17. DNA sequencing of the amplified products exhibited a high level of homology to the corresponding gene from the NCBI public database. Protein expression was conducted in the Escherichia coli, BL21-AI. The recombinant bromelain was then purified in a single step using a Ni-NTA spin column, an example of immobilized metal affinity chromatography. Purified recombinant bromelain was detected by Western blotting. In addition, the purified enzyme exhibited hydrolytic activity towards gelatin and a synthetic substrate, LNPE. The purified recombinant bromelain exhibited optimum activity at pH 4.6 and 45oC.